Eosinophil-to-Neutrophil Ratio Predicts Poor Prognosis of Acute Ischemic Stroke Patients Treated With Intravenous Thrombolysis - Cai, Haoye; Huang, Honghao; Yang, Chenguang; Ren, Junli; Wang, Jianing; Gao, Beibei; Pan, Wenjing; Sun, Fangyue; Zhou, Xinbo; Zeng, Tian; Hu, Jingyu; Chen, Yilin; et al. (Frontiers in Neurology, 2021)
BACKGROUND AND PURPOSE: Eosinophil-to-neutrophil ratio (ENR) recently reported as a novel inflammatory marker in acute ischemic stroke (AIS). However, few studies reported the predictive value of ENR in AIS patients, especially for those with intravenous thrombolysis. METHODS: 266 AIS patients receiving intravenous thrombolysis were retrospectively recruited in this study and followed up 3-month and 1-year. Modified Rankin Scale (mRS) and the time of death were recorded. Poor outcome was defined as mRS 3-6. After excluded for patients lost to follow up, remaining 250 patients were included in the 3-month prognosis analysis and remaining 223 patients were included in the 1-year prognosis analysis. RESULTS: ENR levels in the patients were lower than those in the healthy controls. The optimal cut-off values for the ability of ENR ×102 to predict 3-month poor outcome were 0.74 with 67.8% sensitivity and 77.3% specificity. Patients with ENR×102 ≥ 0.74 have lower baseline National Institutes of Health Stroke Scale (NIHSS) score (median: 7 vs. 11, p < 0.001). After multivariate adjustment, patients with ENR×102 ≥ 0.74 were more likely to come to a better 3-month outcome (OR = 0.163; 95% CI, 0.076-0.348, p < 0.001). At the 1-year follow-up, the patients with ENR×102 ≥ 0.74 showed a lower risk of mortality (HR = 0.314; 95% CI, 0.135–0.731; p = 0.007). CONCLUSIONS: Lower ENR is independently associated 3-month poor outcome, 3-month and 1-year mortality in AIS patients treated with intravenous thrombolysis.